Compliance with the aseptic precautions during intravenous access among the nursing staff at the National Hospital of Sri Lanka (NHSL) - Bataduwaarachchi, Vipula Rasanga; Balasubramanium, Marthani; Balasooriya, Damitha; Senerath, Upul (International Journal of Infection Control, 2010)
Intravenous access is one of the most commonly performed invasive procedures in the clinical practice, during which the improper practice of the aseptic precautions could lead to fatal healthcare associated infections. A descriptive cross sectional study was conducted to assess the compliance with aseptic precautions during intravenous access and to identify the determinants of the substandard practice and practical difficulties encountered at the National Hospital of Sri Lanka using a self administered questionnaire and an observational check list. The majority (60.2%) of the participants fell in to the ‘substandard’ practice category. Compliance for the accepted method of hand washing was 8.4%. Compliance was significantly better among the nursing students (P=0.001), nursing staff that had less experience (P=0.001) and who had updated their knowledge recently (P=0.043). The work load (95.2%) and the shortage of equipment (65.06%) were the main practical difficulties identified. Hand washing practice should be further encouraged in the hospital setting. Continuing education and provisions of the necessary equipment are equally important.